Radial distribution function of the nonideal semiclassical plasma particles - Dyhambaeva, G.S.; Dzhumagulova, K.N.; Ramazanov, T.S. (Recent Contributions to Physics, 2012)
The main problem of the theoretical study of structural properties of the plasma is to obtain the correlation functions of the particles distribution based on a given interaction potential. To solve this problem we used the integral equation of Ornstein - Zernike connecting the radial distribution function with the interaction potential.